KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS THE USE OF POST-EXPOSURE PROPHYLAXIS AMONGST BAR ATTENDANTS AGED 18 TO 35 YEARS IN KAJJANSI TOWN COUNCIL. A CROSS-SECTIONAL STUDY. - Nassanga, Shamim; Nalubega, Jane Frank; Ssemuwemba, Frank; Okwany, Jimmy (Student's Journal of Health Research Africa, 2025)
Background. Post-exposure prophylaxis (PEP) is recommended for HIV-negative persons at high risk of acquiring HIV after occupational or non-occupational HIV exposure. Bar attendants are a risk group for HIV/AIDS due to risky lifestyles such as alcoholism, smoking, rape, and commercial sex. This study aimed at assessing knowledge, Attitude, and Practices towards the use of post-exposure prophylaxis amongst bar attendants aged 18 to 35 years in Kajjansi Town Council. Methodology. A descriptive cross-sectional design was used, involving the quantitative method of data collection using a snowball nonprobability sampling technique to select the study sample. All persons, aged 18+ years who attended bars in the town at the time of the study were included. Data was collected on a daily basis for 7 days and this was from bar attendants in Kajjansi Town Council. Results. Majority of respondents were males 92(92%), 35[35%] of the participants were aged between 25-31, (40%) of the respondents were single. 78 (78%) of participants reported having heard about PEP, and 13 (16.7%) of participants correctly identified occupational exposure as a reason for using PEP. Regarding the attitude, 60 (76.9%) reported that they believe PEP is safe for use, 54 (69.3%) of the participants believed that PEP can prevent HIV/AIDS. Concerning the practices, 42(53.8%) of the participants reported a history of PEP usage and 21(50.0%) of the participants said they obtained PEP from hospitals. Conclusion. Most of the participants had good knowledge about PEP as they very well knew the indications for PEP but had less information about the duration and the exact timing of utilization of PEP. Recommendation. Policymakers should consider public sensitization and awareness Campaigns as a cause to implement the HIV/AIDS reduction and prevention strategies.